Application and Justice: Pathological Effect of the Reason of Means to Ends in the realization of Equal Dignity (Andamios, Revista de Investigación Social, 2014)
The debate over social justice after more than forty years of intense discussion has produced elegant and sophisticated theories of justice; however, it has rendered much fewer significant contributions on what should be the way to translate these theories into the real world. This question places the application of justice as one of the central tasks of the political philosophy of our time. My intention in this paper is to contribute to this task with two conceptual elements, the first of which is the presentation of a structure of practical reasoning oriented to application, which aims at building a guide for application in order to ensure the equal dignity of citizens. The second element intends to introduce the negative impact certain social dynamics have in the operation of the principles of justice, which implies integrating, within the field of the relevant concepts for the application of justice, the way some social phenomena systematically undermine autonomy and freedom.
Keywords: Social justice; administration of justice; social dynamic